(untitled) (International Journal of Engineering and Computer Science, 2014)
Watermarking is the process of embedding data called a watermark into a multimedia object such that watermark can be detected or extracted later to make an assertion about the object. The multimedia object may be an audio, image or video. The aim may be to provide data authentication, data integrity, copyright and so on, depending upon the need. Watermarking can be done either in spatial domain or in frequency domain, the latter one proves to be more efficient than working in the spatial domain. Working with the watermarking in frequency domain requires transformation tools and in this paper we will discuss these various techniques giving more stress on wavelet transforms.